Becoming the mother of a child with disabilities: a systematic literature review. Issue 5 (19th October 2016) - Van Wyk, N. C.; Leech, R.
ABSTRACT: The transition to motherhood starts early in pregnancy and is completed when the mother feels competent in caring for the infant. Becoming the mother of a child with disabilities is demanding as their needs are complex. The aim of the review was to appraise completed qualitative and quantitative reports on the challenges of mothers of children with disabilities regarding their own transition to motherhood. A review of the literature was carried out through, first, a computerized search strategy to identify relevant studies from selected databases and, second, quality appraisal and thematic analysis of selected studies. The transition to motherhood of children with disabilities takes place in the inside world at home, the outside world external to home and the 'going-between' world of travelling between the two worlds. The mothers are challenged at home to integrate basic infant care with technical care of their children. In the outside world they often struggled to ensure that their children got the necessary professional care. Travelling between their homes and healthcare services posed many problems.